Learning styles of teacher candidates: A sample of Firat University - Kazu, Ibrahim Yasar (Academic Journals, 2010)
The aim of the present study is to detect the learning styles of teacher candidates who receive training in the Faculty of Education at Firat University in Turkey. The study is conducted on 446 teacher candidates who are in the first and fourth years in the departments of Primary School Education, Social Studies, Science Education, Art Education, Turkish Language Teaching and Computer and Instructional Technologies Education in the academic year 2008 - 2009. The Kolb Learning Style Inventory was used as the data collection tool in order to detect the learning styles of teacher candidates. Following the analyses, it was found that there is a relation between the classrooms where they receive training and their learning styles. Additionally, it was found that there is not a significant relation between gender, the department of university, alma mater, of the determination of learning styles in advance, the time they started to use computer technology and dominant learning styles.
Keywords: Learning styles; Kolb's learning style; classroom environment